1988
DOI: 10.1038/335142a0
|View full text |Cite
|
Sign up to set email alerts
|

The origin of mutants

Abstract: Nucleic acids are replicated with conspicuous fidelity. Infrequently, however, they undergo changes in sequence, and this process of change (mutation) generates the variability that allows evolution. As the result of studies of bacterial variation, it is now widely believed that mutations arise continuously and without any consideration for their utility. In this paper, we briefly review the source of this idea and then describe some experiments suggesting that cells may have mechanisms for choosing which muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
682
3
11

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,000 publications
(710 citation statements)
references
References 15 publications
14
682
3
11
Order By: Relevance
“…When populations of microorganisms are subjected to non-lethal selection, mutations arise that relieve the selective pressure [35]. This phenomenon, originally called "directed mutation", is now called "adaptive mutation", by which is meant a process that produces advantageous mutations during selection even though other, non-selected, mutations occur at the same time.…”
Section: Adaptive Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…When populations of microorganisms are subjected to non-lethal selection, mutations arise that relieve the selective pressure [35]. This phenomenon, originally called "directed mutation", is now called "adaptive mutation", by which is meant a process that produces advantageous mutations during selection even though other, non-selected, mutations occur at the same time.…”
Section: Adaptive Mutationmentioning
confidence: 99%
“…In their original 1988 paper, Cairns et al hypothesized that mutations could be "directed" toward a useful goal [35]. However, the original evidence supporting this hypothesis has not survived subsequent study.…”
Section: Adaptive Mutations Are Not Directedmentioning
confidence: 99%
“…While such a mechanism seems unprecedented, it should be possible to test whether bacteria behave in the appropriate fashion when challenged with harsh environments. This possibility harkens to the "directed mutation" controversy (Cairns et al, 1988;Andersson et al, 1998;Hendrickson et al, 2002), although in this instance, the mutations are not "directed." Such a model will no doubt prove much easier to advocate than to demonstrate.…”
Section: Discussionmentioning
confidence: 99%
“…MUT 10206 [1][2][3][4][5][6][7] Much of the previous work has involved strains with 44 the FC40 plasmid, which has a frameshift in the lacZ 45 gene and generally reverts by deletion mutation [6][7][8].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Cairns et al [1] noted that reversions of Escherichia frame shift mutations. Cairns originally suggested that 33 mutagenesis was being "directed" toward genes that 34 could allow survival, but the prevailing theory is that 35 the stress of the selective conditions increases mutation 36 rate in non-advantageous and advantageous genes, 37 including the gene(s) leading to prototrophy ("adaptive" 38 mutagenesis).…”
mentioning
confidence: 99%